Functional characterization and target discovery of glycoside hydrolases from the digestome of the lower termite Coptotermes gestroi - Franco Cairo, Joao Paulo L.; Leonardo, Flavia C.; Alvarez, Thabata M.; Ribeiro, Daniela A.; Buechli, Fernanda; Costa-Leonardo, Ana M. [UNESP]; Carazzolle, Marcelo F.; Costa, Fernando F.; Paes Leme, Adriana F.; Pereira, Goncalo A. G.; Squina, Fabio M. (Biomed Central Ltd., 2011)
Background: Lignocellulosic materials have been moved towards the forefront of the biofuel industry as a sustainable resource. However, saccharification and the production of bioproducts derived from plant cell wall biomass are complex and lengthy processes. The understanding of termite gut biology and feeding strategies may improve the current state of biomass conversion technology and bioproduct production.Results: The study herein shows comprehensive functional characterization of crude body extracts from Coptotermes gestroi along with global proteomic analysis of the termite's digestome, targeting the identification of glycoside hydrolases and accessory proteins responsible for plant biomass conversion. The crude protein extract from C. gestroi was enzymatically efficient over a broad pH range on a series of natural polysaccharides, formed by glucose-, xylose-, mannan- and/or arabinose-containing polymers, linked by various types of glycosidic bonds, as well as ramification types. Our proteomic approach successfully identified a large number of relevant polypeptides in the C. gestroi digestome. A total of 55 different proteins were identified and classified into 29 CAZy families. Based on the total number of peptides identified, the majority of components found in the C. gestroi digestome were cellulose-degrading enzymes. Xylanolytic enzymes, mannan-hydrolytic enzymes, pectinases and starch-degrading and debranching enzymes were also identified. Our strategy enabled validation of liquid chromatography with tandem mass spectrometry recognized proteins, by enzymatic functional assays and by following the degradation products of specific 8-amino-1,3,6-pyrenetrisulfonic acid labeled oligosaccharides through capillary zone electrophoresis.Conclusions: Here we describe the first global study on the enzymatic repertoire involved in plant polysaccharide degradation by the lower termite C. gestroi. The biochemical characterization of whole body termite extracts evidenced their ability to cleave all types of glycosidic bonds present in plant polysaccharides. The comprehensive proteomic analysis, revealed a complete collection of hydrolytic enzymes including cellulases (GH1, GH3, GH5, GH7, GH9 and CBM 6), hemicellulases (GH2, GH10, GH11, GH16, GH43 and CBM 27) and pectinases (GH28 and GH29).